2015
DOI: 10.5194/amt-8-4671-2015
|View full text |Cite
|
Sign up to set email alerts
|

An automated cloud detection method based on the green channel of total-sky visible images

Abstract: Abstract.Obtaining an accurate cloud-cover state is a challenging task. In the past, traditional two-dimensional red-toblue band methods have been widely used for cloud detection in total-sky images. By analyzing the imaging principle of cameras, the green channel has been selected to replace the 2-D red-to-blue band for detecting cloud pixels from partly cloudy total-sky images in this study. The brightness distribution in a total-sky image is usually nonuniform, because of forward scattering and Mie scatteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…The lower the aerosol concentration in the sky, the more the sky brightness values tend toward zero. We had compared the brightness distribution between R / B, (B−R) / (B+R), and green channels in our previous study (Yang et al, 2015) and showed the green channel is a better choice for cloud detection, but dark clouds may be misclassified as clear-sky and the sky background in the green channel is still inhomogeneous. To better describe the merit of RAS channel, we compared horizontal brightness distribution of the RAS channel with R / B channel ( Fig.…”
Section: Imaging Device and Rgb Channel Operationmentioning
confidence: 99%
See 3 more Smart Citations
“…The lower the aerosol concentration in the sky, the more the sky brightness values tend toward zero. We had compared the brightness distribution between R / B, (B−R) / (B+R), and green channels in our previous study (Yang et al, 2015) and showed the green channel is a better choice for cloud detection, but dark clouds may be misclassified as clear-sky and the sky background in the green channel is still inhomogeneous. To better describe the merit of RAS channel, we compared horizontal brightness distribution of the RAS channel with R / B channel ( Fig.…”
Section: Imaging Device and Rgb Channel Operationmentioning
confidence: 99%
“…Calculating the solar position requires two basic steps: one is to compute the solar zenith angle and azimuth and the other is to determine the specific coordinates of the sun in the image. The same steps as mentioned in Yang et al (2015) are adopted in this study to accurately calculate the central coordinate of the sun in the TCI image, and then the circumsolar saturated pixels and their circularity can be used to determine whether the sun is visible (Yang et al, 2015). When the sun is blocked, the single threshold algorithm is applied to identify clouds.…”
Section: Dtca Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a number of other ground-based sky imagers have also been developed in other countries and institutes, such as the whole-sky camera (Calbo and Sabburg, 2008;Heinle et al, 2010) and the totalsky cloud imager (Li et al, 2011;Yang et al, 2012Yang et al, , 2015. Most of these sky imagers capture sky conditions with redgreen-blue (RGB) color images named all-sky images, and are successfully applied to estimate cloud cover.…”
Section: Q LI Et Al: From Pixels To Patchesmentioning
confidence: 99%